2010
DOI: 10.1007/s10661-010-1816-6
|View full text |Cite
|
Sign up to set email alerts
|

Surveying drainage culvert use by carnivores: sampling design and cost–benefit analyzes of track-pads vs. video-surveillance methods

Abstract: Environmental assessment studies often evaluate the effectiveness of drainage culverts as habitat linkages for species, however, the efficiency of the sampling designs and the survey methods are not known. Our main goal was to estimate the most cost-effective monitoring method for sampling carnivore culvert using track-pads and video-surveillance. We estimated the most efficient (lower costs and high detection success) interval between visits (days) when using trackpads and also determined the advantages of us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…In a two-year study, involving 260 km of highways and 314 km of national roads, Grilo et al (2009) found that only 2.5% out of 806 detected casualties of carnivores were of polecats and suggested that this might be positively correlated with the species abundance in the region. This conclusion agrees with both Grilo et al (2008), in which from a total of 1,940 track records of carnivores detected in highway culverts and underpasses (marble dust track pads) only one corresponded to a polecat, and Mateus et al (2010), a study conducted in the same area, to assess cost-effectiveness of monitoring methods of carnivore use of drainage culverts, in which not a single polecat was recorded.…”
Section: Distribution and Statussupporting
confidence: 84%
“…In a two-year study, involving 260 km of highways and 314 km of national roads, Grilo et al (2009) found that only 2.5% out of 806 detected casualties of carnivores were of polecats and suggested that this might be positively correlated with the species abundance in the region. This conclusion agrees with both Grilo et al (2008), in which from a total of 1,940 track records of carnivores detected in highway culverts and underpasses (marble dust track pads) only one corresponded to a polecat, and Mateus et al (2010), a study conducted in the same area, to assess cost-effectiveness of monitoring methods of carnivore use of drainage culverts, in which not a single polecat was recorded.…”
Section: Distribution and Statussupporting
confidence: 84%
“…For instance, little is known about the consequences of vibration and noise on biodiversity living adjacent to the railway bed (see Chap.6). Also, studies are needed on the relative cost-effectiveness of different management tools and mitigation measures to help reconcile environmental protection and socio-economic demands (see, e.g., Andreassen et al 2005;Ford et al 2009;Mateus et al 2011). The potential positive impacts of railways also need to be better explored, including in particular the prospective for the right-of-way to act as a shelter for biodiversity (see Chap.…”
Section: Railways Travel Towards Environmental Sustainabilitymentioning
confidence: 99%
“…One method that allows for the evaluation of how water affects the extent culverts are used by carnivores to cross roads is video-surveillance (Stewart et al 1997;Mateus et al 2011). This method also has the advantage of being able to record an animal's behavior towards the culvert itself (see Hardy et al 2003;Dodd et al 2007), which can yield valuable insights regarding culvert design as a road mitigation measure.…”
Section: Introductionmentioning
confidence: 99%